Epithelioid Sarcoma Presenting as Recurrent Thumb Ulcer: A Lesson to Learn - Rajeev, Lakkavalli Krishnappa; Asati, Vikas; Mallekavu, Suresh Babu; Babu, K Govind; Champka, G (Indian Journal of Medical and Paediatric Oncology, 2018)
Epithelioid sarcoma (ES) first described by Enzinger in 1970,1 is a rare soft-tissue sarcoma typically presenting as a subcutaneous or deep dermal mass in distal portions of the extremities of adolescents and young adults. They are frequently mistaken for ulcers, abscesses, or infected warts that fail medical management. Patients often develop multiple local recurrences of long duration, with subsequent metastases in 30%–50% of cases.2 We here report a case of left thumb ES that presented as an ulcer and subsequently metastasized to the forearm, arm, axillary lymph nodes, and lungs.
Keywords: Distal type sarcoma; epithelioid sarcoma; hand sarcoma; thumb ulcer